The Effect of Talent Management, Performance Incentives, and Recognition Programs on Employee Productivity in the Retail Industry in Central Java - Budi Sulistiyo Nugroho; Annasit Annasit; Farid Alfalaki Hamid; Zami Furqon; Agus Setyono (Westscience Press, 2025)
This study investigates the effects of Talent Management, Performance Incentives, and Recognition Programs on Employee Productivity within the retail industry in Central Java, Indonesia. Utilizing a quantitative research design, data were collected from 210 employees using a 5-point Likert scale and analyzed with Structural Equation Modeling (SEM-PLS 3). The results reveal that Recognition Programs had the most significant effect on Employee Productivity, followed by Performance Incentives, and Talent Management. These findings indicate that non-monetary rewards such as employee recognition programs play a pivotal role in motivating employees and enhancing their performance. The study highlights the importance of integrating recognition efforts with performance incentives and talent management strategies to achieve optimal productivity. Practical recommendations are provided for retail companies in Central Java to enhance employee motivation and organizational effectiveness.